Modeling and optimization of biodegradation of methylene blue by Staphylococcus aureus through a statistical optimization process: a sustainable approach for waste management. (11th July 2022) - Ayed, Lamia; Bekir, Karima; Jabeur, Chedia
Bacterial species for metabolizing dye molecules were isolated from textile wastewater. The best microbial species for such an application was selected amongst the isolated bacterial populations by conducting methylene blue (MB) batch degradation studies with the bacterial strains. The most suitable bacterial species was Staphylococcus aureus ( S. aureus ). Process parameters were optimized using Full Factorial Design (FFD) and under the optimum conditions (pH of 5, temperature of 35 °C, 150 ppm, and time of 8 h). Response Surface Methodology (RSM) modeling technique was applied to model the process and their performance and predictive capabilities of the response (removal efficiency) was also examined. When tested with 20 ppm dye using batch reactors, the maximum COD and color removal efficiencies, were found to be 88% and 98%, respectively. Our results showed that Staphylococcus aureus had a high decolorization capacity. UV-Visible and Fourier-transform infrared (FTIR) spectroscopy analysis confirmed the biodegradation of MB. Using phytotoxicity and mutagenicity endpoints, toxicological studies of MB before and after biodegradation were studied. Toxicity assay signaled that biodegradation led to the detoxiﬁcation of MB dye. HIGHLIGHTS: In the present investigation, the dye was degraded by Staphylococcus aureus using FFD. RSM modeling technique was applied to model the process. Staphylococcus aureus was isolated from the effluent treatment plant of a textile. The degradation products were characterized by UV-Visible and FTIR. Phytotoxicity and mutagenicity assay signaled that biodegradation led to detoxification of MB dye. Graphical Abstract